Surface-Water Quality of the Gulf of Papagayo, North Pacific, Costa Rica - Saravia Arguedas, Ana Yury (2021)
In recent years, the northwestern part of the North Pacific areas of Costa Rica has undergone rapid socioeconomic development. This situation, combined with the scarce available information about the water quality of the Gulf of Papagayo, became the starting point to carry out a study to investigate the spatiotemporal variations of physicochemical and biological parameters of surface waters. Seven samplings were collected during the dry season and the rainy season from October 2016 to February 2018. Water quality parameters such as: temperature, salinity, dissolved oxygen, and chlorophyll a of six analytes: nitrate, nitrite, ammonia, phosphate, silicate and biological oxygen demand were measured. The results showed that phosphate and ammonium levels were lower during the rainy season (<6 µg P-PO4−3 L−1–9.53 µg P-PO4−3 L−1 and <11 µg N-NH4+ L−1–9.57 µg N-NH4+ L−1) than during the dry season (<6 µg P-PO4−3 L−1–13.64 µg P-PO4−3 L−1 and <11 µg N-NH4+ L−1–14.43 µg N-NH4+ L−1), which may be related to low rainfall (0, 00–26, 16 mm) during the sampling period. The dry season showed enrichment of ammonium, phosphate, and chlorophyll a due to the influence of the coastal upwelling for the intensification of the Papagayo winds from December to March. The physical, chemical, and biological indicators demonstrated that the Gulf waters had adequate quality. Nonetheless, there are specific areas such as Culebra Bay with conditions that could show deterioration of water quality.